Community management as an essential tool in the protection and conservation of archaeological heritage - Arroyo Wong, María Gabriela (2017)
"Revaluation" becomes a key concept when conservation and protection of the Cultural Heritage and specifically of the Archaeological Heritage is spoken. In this way, community management is an essential tool since it allows community-heritage integration. The active participation of the members of the communities leads to a real process of identification with the patrimony and therefore in actions and processes that are maintained in the long term.